Internet of Things Based Control and Monitoring LCD Projector for Smart Class Room Concept - Wibawa, Kadek Suar; Wirabuana, Putu; Wiranatha, A. A. K. Agung Cahyawan (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
The Smart Class Room concept requires modern technology to control and monitor Liquid Crystal Display Projector devices. This technology can be created by implementing the Internet of Things. The LCD Projector can be controlled remotely via an android-based mobile application. Research and Development is the right method to produce prototypes. The results of the implementation of the system show that remote control via the internet using a realtime firebase database can be achieved in 3 seconds. The distance between the LCD Projector and the embedded system device can communicate well up to 2 meters using the Infrared sensor. Changes in Temperature and Ambient Light intensity can be detected within 500mS measurement time. Current detection shows 4 LCD status modes: ON, OFF-Fan On, Stand by and Off. Keywords : Smart Class Room, Internet of Things, Monitoring LCD, Current Detection, Mobile App